FEATURES OF COMORBIDITY OF INTERNAL DISEASES IN MILITARY PERSONNEL PARTICIPATING IN THE ANTI-TERRORIST OPERATION/JOINT FORCES OPERATION - Seliuk, O.V. (World of Medicine and Biology, 2021)
Comprehensive assessment of comorbidity is an urgent problem of modern medicine and is aimed at prolonging the professional longevity of the working-age population. 183 military personnel participating in the Anti-Terrorist Operation/Joint Forces Operation who were undergoing treatment for arterial hypertension were retrospectively examined by random sampling. The features of comorbid pathology of internal organs were determined according to the Cumulative Illness Rating Scale (CIRS), depending on the stage of arterial hypertension. The results of the study are intended for medical and social justification of optimization of the functional and organizational model of comorbid pathology prevention to prolong the professional longevity of military personnel, their suitability for military service for health reasons.
Keywords: arterial hypertension; comorbid pathology; chronic diseases; combatants; modern armed conflicts